Ageing & Sports - Müller P; 2; 3; Stiebler M; Schwarck S; 3; Haghikia A; 2; 4; Düzel E; 3; 4 (Deutsche Zeitschrift für Sportmedizin)
Physical activity is a low-cost intervention in primary and secondary prevention of numerous chronic diseases (e.g., cardiovascular diseases, metabolic diseases, sarcopenia, cancer, dementia). Furthermore, several epidemiological, observational and randomized controlled studies have shown positive effects of physical activity on cognition and reduced risk of neurodegenerative diseases.Industrial societies are currently experiencing a tremendous demographic change with an unprecedented increase in absolute and relative numbers of elderly adults. This demographic change entails a plethora of challenges for the healthcare system. As the prevalence of many (neurodegenerative) diseases correlates with age, the number of persons affected by age-related diseases will rise.In this context, non-pharmacological concepts of healthy aging are becoming more attention. Especially lifestyle interventions (e. g. physical activity) are becoming increasingly important and could play a key role in healthy aging and prevention of neurodegenerative diseases. Recent research has shown that physical activity and/or physical exercise benefits cognition and brain plasticity across the lifespan.In this review we summarize (i) the effects of physical activity and/or physical exercise on brain plasticity, (ii) the role of physical activity and/or physical exercise in the prevention and therapy of dementia, and (iii) potential neurobiological mechanisms of physical activity-induced brain plasticity.Key Words: Age-related Diseases, Brain Plasticity, Physical Exercise, Prevention